Tarpasmeninės komunikacijos su klientais ypatumai teikiant elektronines paslaugas bibliotekose - Janavičienė, Daiva; Sinušaitė, Milda (Information & Media, 2011)
Bibliotekos paslaugų modernėjimas siejamas su elektroninės prieigos galimybių plėtra. Naudojant Saityno 2.0 technologijas, aktualūs komunikacijos įgūdžiai, kurie elektroninėje erdvėje nėra analogiški tiesioginės komunikacijos su klientais atvejams. Remiantis I. Rowlandsu, D. Nicholasu ir P. Williamsu, straipsnyje charakterizuojami elektroninių paslaugų klientai. Naudojant J. Nielseno tyrimo rezultatus, išskiriami elektroninės komunikacijos su klientais ypatumai, kuriuos sudaro operatyvumas, galimybė gauti paslaugas sau patogioje vietoje ir reguliuoti komunikacijos greitį, tiesioginio kontakto nebuvimas, anonimiškumas, konsultavimo sudėtingumas, pirmenybė elektroninių dokumentų naudojimui. Ypatumų raišką iliustruoja empiriniais apklausos (anketavimo) ir interviu tyrimo metodais atlikti tyrimai Klaipėdos apskrities viešojoje Ievos Simonaitytės bibliotekoje. Reikšminiai žodžiai: viešoji biblioteka, bibliotekų elektroninės paslaugos, tarpasmeninė elektroninė komunikacija. Electronic services in libraries: characteristics of communication with clients Daiva Janavičienė, Milda Sinušaitė Summary The object of the investigation is electronic communication between library workers and clients. The goal is to analyze the characteristics of communication with clients in libraries by exploring the practice of Klaipėda district Ieva Simonaitytė public library, Lithuania. The main tasks are as follows: 1) to analyze the concept of electronic services in respect of communication; 2) to study the ways in which libraries communicate with their clients in the electronic environment; 3) to investigate the characteristics of clients who use electronic services, their behaviour and needs; 4) to identify the main features of electronic communication between libraries and their clients; 5) to investigate the characteristics of electronic communication with clients in the Klaipėda district I. Simonaitytė public library and to offer recommendations. On the grounds of literature survey and interview analysis and using the method of synthesis, it was possible to draw a conclusion that the communication between workers and clients on the internet has some particular characteristics: speed, the possibility to get a service at the place where it is comfortable, and to regulate the speed of communication, absence of direct contact, difficulty of consultation, preference of electronic documents. Taking into account these specific characteristics, libraries improve the quality of internet services, expand the spectrum of services, change their image and establish community-based relationships with clients. The research has shown that the characteristics of electronic communication, identified in the theoretical part, exist in the practice of Klaipėda district I. Simonaitytė library. Keywords: public libraries, electronic services, electronic interpersonal communication. /span>